Factors Contributing to Popularity of Loyalty Programs: Evidence From Emerging Markets. (May 2016) - Yan, Wei; Cui, Zhijian
Using secondary data from multiple sources, this study empirically examines the factors that contribute to the popularity of loyalty programs in the airline and hotel industries in the context of emerging market economies. We find that the number of partners, the number of redemption options, and the threshold for obtaining elite status all positively contribute to a loyalty program's popularity. However, the award redemption requirement has the opposite effects on a program's popularity. Our results show that the redemption requirement of top-tier preferential treatment negatively affects the program's popularity. Surprisingly, the redemption requirement of entry-tier preferential treatment positively affects the program's popularity. As one of the few program-level empirical studies, this study contributes new insights to the extant literature on loyalty program management and provides managerial guidelines for practitioners in the hospitality sector.